Visibility of epidermoid tumors on steady-state free precession images. - Sakamoto, Y; Takahashi, M; Ushio, Y; Korogi, Y (American Journal of Neuroradiology, 1994)
PURPOSE To determine whether steady-state free precession sequences improve the MR visibility of epidermoid tumors in comparison with spin-echo images. METHODS Patients were four women and three men with epidermoid tumors in the subarachnoid spaces. MR was performed with a 1.5-T superconductive unit. For steady-state free precession imaging, three-dimensional Fourier transform fast imaging with steady-state free precession (FISP) images were used (20-40/7 [repetition time/echo time], flip angle of 25 degrees). The visualization and contrast-to-noise ratio were compared in FISP images and spin-echo images. In one case, the images of FISP and fast low-angle shot were obtained with variable repetition times and flip angles to evaluate the best pulse sequences for the visualization of epidermoid tumors. RESULTS The contrast-to-noise ratios between tumors and cerebrospinal fluid ranged from 7.9 to 17.5 (average was 12.9) on FISP images. The average of contrast-to-noise ratios on T1, T2, and proton density-weighted spin-echo images were 1.6, 2.0, and 4.2, respectively. Three-dimensional Fourier transform FISP images best showed central nervous system and demonstrated epidermoid tumors excellently. CONCLUSIONS Epidermoid tumors in the subarachnoid spaces were better demonstrated on steady-state free precession (three-dimensional Fourier transform FISP) than on conventional spin-echo images.